Sistem Pendukung Keputusan Dengan Menerapkan Metode Multi-Attribute Utility Theory Pada Pemilihan Content Writer - Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Content Writer is an important profession in the process of creating interesting content. The definition of Content Writer is a professional writer whose job is to write concepts of interesting content which will eventually be produced in online media. The income that is large enough for this profession results in many people being interested in working in that field. Therefore it will be difficult for those who open jobs in the field of Content Writers to choose who should be chosen. To select Content Writer candidates, it is better to use a system so that with this system it can help interested parties so that the results of the selection are not subjective or impartial. A good system to use is a decision support system. decision support system (DSS) is the development of an information system using the same way of working as an information system, namely a computer-based system. This SPK can be used in conjunction with supporting methods such as the MOORA method, the PSI method and so on. In this study the method used is the DEATH method. The MAUT method or the Multi-Attribute Utility Theory (MAUT) method is a method that prioritizes quality as a comparison so that the quality of each criterion will be considered as the first choice. Based on the calculation results from the MAUT method, a result of 0.6701 is obtained with the alternative A3 On behalf of Aldi as the best alternative that deserves to be accepted as a content writer.